Hindu Goddesses : beliefs & Practices - Foulston, Lynn (Sussex Academic Press, 2019)
This book explores the diversity of Hindu goddesses and the variety of ways in which they are worshiped. Although they undoubtedly have ancient origins, Hindu goddesses and their worship is still very much a part of the fabric of religious engagement in India today. The book offers an introduction to a complex and often baffling field of study. Part I, "Beliefs" provides a series of encounters with a range of Hindu goddesses starting with the idea of 'Goddess' as a philosophical concept. Topics include textual evidence for belief structures, goddess mythology, and the importance of 'the Goddess' in Tantrism. Part II, "Practices" leads the reader through the tangled web of goddess worship, pausing along the way to examine the contrast between temple and local worship, the splendour of festivals and the importance of pilgrimage to those places in India where goddesses are considered to reside. A Conclusion provides details of contemporary developments in goddess worship, such as the appearance of new deities who supply the needs of worshipers in the twenty-first century. No prior knowledge is necessary as the book is aimed at undergraduate students and anyone interested in the religions and philosophy of India.